PENGEMBANGAN MEDIA COOL APPLICATION POWERPOINT INTERACTIVE PADA TEMA 6 ENERGI DAN PERUBAHANNYA DI KELAS III SD - Reza Sukma Dewi; Daniah; Nida Jarmita (FITRAH: International Islamic Education Journal, 2022)
The limited availability of learning media and the lack of varied media in schools greatly affect the student learning process. Meanwhile, judging from the learning styles of third grade elementary school students tend to follow the audio-visual learning style, meaning that students can learn optimally if there is an audio-visual-based learning media. One of the media that can be developed is media cool application powerpoint interactive. The aims of this study were (1) to determine the design of the development of cool application powerpoint interactive media on the 6 energy theme and its changes in class III SD, (2) to determine the feasibility of the cool media application powerpoint interactive media for students on the 6 energy theme and its changes in class III SD, ( 3) find out the response of teachers and students to the cool application powerpoint interactive media on theme 6 energy and its changes in grade III SD. This type of research is Research and Development, which uses a 4D model with 4 stages, namely define, design, develop and disseminate. The research instruments were media expert validation sheets, material expert validation sheets, teacher response questionnaires and student response questionnaires. The results showed (1) the results of media validation obtained a score of 100% with a very feasible category (2) the results of material validation obtained a score of 80% with a decent category, (3) the results of media and material validation by the teacher obtained a score of 100% with a very decent category. and (4) the results of the teacher's response with a score of 100% with a very decent category and the results of student responses with a percentage of 96% with a very decent category. Based on the results of these data, it can be concluded that the development of cool media application powerpoint interactive on theme 6 energy and its changes in class III SD is very feasible to use.